Analisis Pendapatan dan Evaluasi Penyerapan Anggaran pada Puskesmas dalam Rangka Efisiensi Pengelolaan Keuangan Daerah - Nadhir, Athiyya Umareta; Widodo, Condro (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
Revenue audits and budget absorption evaluations are important instruments in assessing the efficiency of financial management in public service entities such as Community Health Centers (Puskesmas). This study aims to analyze the implementation of revenue audits by Public Accounting Firms (KAP) and evaluate budget absorption in Puskesmas as an effort to improve the efficiency of regional financial management. The method used is a descriptive qualitative approach through observation and documentation of audit reports and budget realization reports. The main income of Puskesmas comes from capitation funds, non-capitation funds, and health service levies. According to the audit results, there is a negative deviation percentage in the realization of capitation income of ±80%. In addition, budget absorption in Puskesmas is not optimal due to funding delays and inappropriate planning. Budget absorption is not optimal due to funding delays and inappropriate planning. This study emphasizes the importance of strengthening financial information systems, improving human resource competencies, and harmonizing regulations to improve regional financial efficiency and accountability